How Ireland Voted 2020
L, 374 p. 89 illus. in color.
Keywords: This book is the 9th volume in the established How Ireland Voted series and provides the definitive story of Ireland’s mould-breaking 2020 election. For the first time ever, Sinn Féin won the most votes, the previously dominant parties shrank to a fraction of their former strengths, and the government to emerge was a coalition between previously irreconcilable enemies. For these reasons, the election marks the end of an era in Irish politics. This book analyses the course of the campaign, the parties’ gains and losses, and the impact of issues, especially the role of Brexit. Voting behaviour is explored in depth, with examination of the role of issues and discussion of the role of social cleavages such as class, age and education. The process by which the government was put together over a period of nearly five months is traced through in-depth interviews with participants. And six candidates who contested Election 2020 give first-hand reports of their campaigns. Michael Gallagher is Professor of Comparative Politics in Trinity College Dublin, Ireland. Michael Marsh is Emeritus Professor of Political Science in Trinity College Dublin, Ireland. Theresa Reidy is Senior Lecturer in Government at University College Cork, Ireland.